Correlation between second trimester beta human chorionic gonadotropin levels and pregnancy outcome in high risk group - Sharma, Praveen; Maheshwari, Sunita; Barala, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Current obstetric practice uses second trimester maternal serum levels of alpha fetoprotein, beta human chorionic gonadotropin (b hCG), unconjugated estradiol as a screening tool for fetal aneuploidy. Given the obvious role of placenta in determining the maternal serum levels of these hormones, we evaluate their role as predictors of placental dysfunction as manifested by pregnancy outcome. Methods: This prospective study was done in department of obstetrics and gynecology, RNT Medical College, Udaipur, Rajasthan on 150 patients attending the antenatal OPD and those admitted between 16 to 20 weeks of pregnancy. Mid-trimester serum b hCG levels was obtained in these patients. They were followed up till delivery or abortion to see for development of any obstetrical complication. Results: Out of 100 cases in study group, 17% cases had level of serum b hCG >2 MOM and 83% cases had < 2 MOM. Out of 50 cases in control group, 8% cases had level of serum b hCG >2 MOM and 92% cases had < 2 MOM. Out of 17 cases in study group with high level of serum b hCG, 82.35% and 0% out of 4 cases in control group, developed PIH. Out of 17 cases with high level of b hCG in study group, 58.85% and 25% out of 4 cases in control group, developed IUGR. Conclusions: Women with bad obstetric history and unexplained elevation of serum b hCG during second trimester are at an increased risk for PIH and IUGR.